Strategies for Reading Comprehension: A Review of Studies in Latin America - Armijos Uzho, Angie (2023)
Reading comprehension is one of the most important challenges in Latin American education because a considerable number of students have difficulties in reading, analyzing and discussing academic texts. In most cases, there has been evidence of a poor application of methodological strategies by teachers in educational institutions so that students can adequately understand and synthesize the information studied throughout the academic cycles. Currently, young people read mainly out of obligation or academic commitment, since the teacher requests it as an evaluative requirement of some activity, but not as a practice of general interest that promotes understanding, deduction and later the construction of knowledge with significant learning. Therefore, the methodology of this research focused on analyzing, through a qualitative approach, twenty scientific articles stored in the Redalyc database through a systematic review, where it is intended to determine the most innovative and technological strategies such as the arborigram, paraphrasing, infographics, comics, online graphic organizers and music as an attractive element that allow teachers together with their students to achieve a correct reading comprehension and encourage young people to that they get a reading habit by taking advantage of their mobile devices.